دلالات الإعجاز البياني للآيات المتشابهة في قصة آدم عليه السلام: دراسة تحليلية Implications of the Literary Inimitability of Mutashābih Verses in the Story of Adam: An Analytical Study - الأطرش رضوان جمال; مخلوف حسام الدين (Journal of Islam in Asia (E-ISSN 2289-8077), 2016)
الملخّص تتناول هذه الدراسة الآيات المتشابهة في قصة آدم عليه السلام من حيث الإعجاز القرآني البياني فيها، حيث حلَّل الباحثان تلك الآيات القرآنية، ووقفا على أسرارها البلاغية والبيانية والدلالية. وتتجلى أهمية هذا الموضوع في كونه يكشف عن دلائل إعجاز القرآن الكريم. واعتمدت هذه الدراسة على المنهج الاستقرائي في جمع الآيات القرآنية المتشابهة من القصة، وما تعلق بها من نصوص تفسيرية، ومن ثم المنهج التحليلي لاستخلاص أهم الدلالات البيانية. ومن أهم ما توصَّل إليه الباحثان أنَّ التعبير القرآني في الآيات المتشابهة في قصة آدم جاء في أعلى درجات البلاغة والبيان، فالحرف الواحد في هذه الآيات معجز في موضعه الذي لا يغني عنه غيره في تماسك الكلمة، وكذلك الكلمة في تماسك الجملة، والجملة في تماسك الآية، والآيات في تماسك السورة. الكلمات المفتاحية: القرآن الكريم، الإعجاز البياني، المتشابه اللفظي، قصة آدم، الدلالات. Abstract This study deals with Mutashābih verses in the story of Adam (peace be upon him) in terms of their miraculous content contained therein. The researchers analysed those Qur’anic verses to discover their rhetorical and semantic secrets. The importance of this topic is its revealing dimensions of the miracle of the Qur’an. This study uses on inductive approach in collecting Mutashābih verses of the story of Adam (peace be upon him) with recourse to explanatory texts. It also uses the analytical method to extract the most important semantic and rhetorical implications. Among the most important findings is that the Mutashābih verses in the story of Adam (peace be upon him) are of the highest degree of eloquence. Every letter in such verses is miraculously positioned in its place and cannot be replaced by other letters in the cohesion of the word, just as the word is in its right place for the cohesion of the sentence, and the sentence in the cohesion of the verse and verses in the cohesion of the SËrah. Keywords: the Qur’an, Linguistic Inimitability, Literal Mutashābih, the story of Adam, Evidences.